PENGARUH KAPASITAS INDIVIDU TERHADAP BUDGETARY SLACK PADA PERUSAHAAN FINANCE DI KOTA BENGKULU - Ismacoryanata Ismacoryanata (Jurnal Akuntansi, 2017)
This study aims to examine the effect of education, training, and experience on budgetary slack on finance companies in the city of Bengkulu. The benefits of the research to be achieved include an input for the management of the company as a consideration in developing a human resource capacity development strategy. The awareness that slack should be reduced is very important because it will help budget makers use their resources efficiently and effectively. This research method is a survey method. The sampling method used purposive sampling method as many as 10 finance companies in the city of Bengkulu with 40 respondents.The research data was analyzed using multiple regression which was first tested for data quality and classical assumptions. The results obtained show that education, training, and experience have a negative impact on budgetary slack in finance companies in Kota Bengkulu.Keywords: Individual Capacity, Budgetary Slack, Finance Company